The tutor in the virtual campus as a new educational model based on education and information technologies at the Universidad Andina del Cusco - Alfaro Aucca, Crayla; Corahua Ordóñez, Jessika; Pezúa Vásquez, Rocío Liney; Pacheco-Mendoza, Josmel Roy (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2022)
Objective: Identify and analyze the technological and academic needs of the undergraduate students of the Universidad Andina del Cusco (UAC) for the proposal of new educational models based on Information Communications Technology (ICT)and the performance of the tutor in virtual environments. Learning. Originality/contribution: The analysis argues the importance and versatility of the virtual environment for the teaching-learning process as well as the challenges of remote immersion in a high Andean town to virtual learning environments (AVA).  Method: Methodological triangulation was used to identify the academic and technological needs of undergraduate students with a total of 6194 students from the central headquarters and the three affiliates of the university, through the survey technique for data collection and documentary analysis. of the proposal for the creation of the virtual campus. Strategies/information collection: The survey of academic and technological needs carried out by the Department of Academic Development in the period 2020-2021, period of implementation of distance education due to global health emergency, was taken as a basis. Conclusions: The importance of identifying the technological and academic needs of undergraduate students has allowed reducing the academic-technological gaps based on the proposal of a platform with digitally created pedagogical spaces such as the campus and virtual classroom, which helped increase quality. of distance training processes.